KONSEP AUPB UNTUK KEAMANAN DATA DALAM STANDARDISASI DAN SISTEM GEOCODING ALAMAT PERKOTAAN DAN PERDESAAN INDONESIA - Widowati, Dyah Ayu; Sutanta, Heri; Diyono, Diyono; Atunggal, Dedi; Laksono, Dany; Sumaryono, Sumaryono; Mustofa, Fakhruddin (Universitas Kristen Satya Wacana, 2023)
This article aims to formulate the embodiment of the AUPB concept in the standardization and geocoding system of Indonesian urban and rural addresses. Furthermore, it analyses the synchronization of data security principles in standardization and geocoding systems for urban and rural addresses in Indonesia. Conceptually, the process of address standardization and geocoding in the context of AUPB is closely related to the orderly administration of government, accountability of government agencies and/or officials, and implementation of statutory provisions. Overall, the element of AUPB that plays the most role in the standardization process and the address geocoding system is the principle of legal certainty. The principle of openness is attached to data security, and both are synchronized in implementing standardization and geocoding systems for urban and rural addresses in Indonesia. Even though all columns in the address database are stored in Elasticsearch, only specific columns can be accessed by general users through the Geocoding System website. Hence, the addresses presented are general data and do not contain personal data.